2007
DOI: 10.3324/haematol.10758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of histone deacetylase inhibitor valproic acid on progenitor cells of acute myeloid leukemia

Abstract: Histone deacetylase inhibitor valproic acid (VPA) was recently shown to enhance proliferation and self-renewal of normal hematopoietic stem cells, raising the possibility that VPA may also support growth of leukemic progenitor cells (LPC). Here, VPA maintains a significantly higher proportion of CD34 + LPC and colony forming units compared to control cultures in six AML samples, but selectively reduces leukemic cell numbers in another AML sample with expression of AML1/ETO. Our data suggest a differential effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…40,41 Similarly, VPA may enhance, in vitro, clonogenic capacity of CD34 þ AML progenitor cells. 42,43 Our findings explain the poor outcome of AML patients and even several cases of rapid disease progression in clinical studies using VPA. 23,40 Our observations again uncouple differentiation from APL eradication and have important new implications for the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 66%
“…40,41 Similarly, VPA may enhance, in vitro, clonogenic capacity of CD34 þ AML progenitor cells. 42,43 Our findings explain the poor outcome of AML patients and even several cases of rapid disease progression in clinical studies using VPA. 23,40 Our observations again uncouple differentiation from APL eradication and have important new implications for the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 66%
“…Our results suggest that this principle may also be true for primitive FLT3-ITD þ progenitors from AML. This counterproductive effect on leukemic stem/progenitor cells has also been reported for other novel treatment strategies in AML, such as the histone deacetylase inhibitor valproate (39).…”
Section: Discussionmentioning
confidence: 91%
“…leukemic progenitor population increased after VPA treatment, resulting in stabilization of the leukemic stem cell compartment, 47 while Mahlknecht et al showed that treatment with VPA mobilizes leukemic blast cells from the bone marrow compartment due to reduced VLA-4 expression. 48 We further investigated the effect of HDAC inhibition on progenitor differentiation using colonyforming assays and by analyzing progenitor populations during neutrophil development.…”
Section: Discussionmentioning
confidence: 99%